Pengaruh Komunikasi, Kompensasi, dan Disiplin Kerja Terhadap Produktivitas Kerja PT. Mastar Samudera Rejeki Pare - Silvia Dwi Era Safira; Debby Santyo Rusandy; Iing Sri Hardiningrum (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
Abstract : This research aims to determine the effect of communication, compensation and work discipline on the work productivity of PT. Mastar Samudera Rejeki Pare. The technique used is quantitative. The population used in this research was 34 employees of PT. Mastar Samudera Rejeki Pare. The sampling technique uses a saturated sample method, namely non-probability sampling. Information processing in this research uses device testing, classical assumption testing, influence testing, and hypothesis testing. The results of this research are that communication has a partial influence on work productivity with a significance value of 0.000 < 0.05, compensation has a partial influence on work productivity with a significance value of 0.000 < 0.05, work discipline has a partial influence on work productivity with a significance value of 0.000 < 0,05, overall communication variable. compensation, and work discipline have a simultaneous effect on work productivity with a value of 0.000 < 0.05.